Inactivation of Zona Incerta Blocks Social Conditioned Place Aversion and Modulates Post-traumatic Stress Disorder-Like Behaviors in Mice - Zhou, Hong; Xiang, Wei; Huang, Mengbing (Frontiers in Behavioral Neuroscience, 2021)
Zona incerta (ZI), a largely inhibitory subthalamic region connected with many brain areas, has been suggested to serve as an integrative node for modulation of behaviors and physiological states, such as fear memory conditioning and aversion responses. It is, however, unclear whether ZI regulated the repeated social defeat stress (RSDS)-induced social conditioned place aversion (CPA) and post-traumatic stress disorder (PTSD)-like behaviors. In this study, the function of ZI was silenced via bilateral injection of tetanus toxin light chain (Tet-tox), a neurotoxin that completely blocks the evoked synaptic transmissions, expressing adeno-associated viruses (AAVs). We found ZI silencing: 1) significantly blocked the expression of RSDS-induced social CPA with no effect on the innate preference; 2) significantly enhanced the anxiety level in mice experienced RSDS with no effect on the locomotion activity; 3) altered the PTSD-associated behaviors, including the promotion of spatial cognitive impairment and the preventions of PPI deficit and social avoidance behavior. These effects were not observed on non-stressed mice. In summary, our results suggest the important role of ZI in modulating RSDS-induced social CPA and PTSD-like behaviors.